On the secrecy performance of integrated satellite‐aerial‐terrestrial networks. (28th January 2020) - Cheng, Guoqiang; Huang, Qingquan; Xing, Ruiyang; Lin, Min; Upadhyay, Prabhat K.
Summary: This paper investigates secure transmission of an integrated satellite‐aerial‐terrestrial network (ISATN), where multiple eavesdroppers (Eves) attempt to overhear the satellite signals cooperatively. The ISATN adopts an unmanned aerial vehicle (UAV) equipped with multiple antennas as a relay with threshold‐based decode‐and‐forward (DF) protocol. By assuming that perfect instantaneous channel state information (CSI) of the satellite‐UAV link and the statistical CSI of the UAV‐user link are available, we first propose a beamforming (BF) scheme for maximizing the achievable secrecy rate (ASR) of the considered network. Then, we derive the analytical expressions of the secrecy outage probability (SOP) and ergodic secrecy rate (ESR) of the considered system with the BF strategy under an assumption that the satellite‐UAV link undergoes the shadowed‐Rician fading, while the UAV‐user link experiences the correlated Rayleigh fading. Finally, numerical results are given to demonstrate the superiority of the proposed BF scheme against zero forcing (ZF) and maximal ratio transmission (MRT) schemes and the validity of the secrecy performance analysis. Abstract : This paper investigates secure transmission of an integrated satellite‐aerial‐terrestrial network, a secure beamforming scheme is proposed and the the secrecy outage probability and ergodic secrecy rate of the consideredsystem are analyzed.